Energy cost of walking in obese survivors of acute lymphoblastic leukemia: A report from the St. Jude Lifetime Cohort - Matthew D. Wogksch; Emily R. Finch; Vikki G. Nolan; Matthew P. Smeltzer; Fawaz Mzayek; Chelsea G. Goodenough; Ching-Hon Pui; Hiroto Inaba; Daniel A. Mulrooney; Daniel A. Mulrooney; Sue C. Kaste; Sue C. Kaste; et al. (Frontiers Media S.A., 2022)
PurposeAdult survivors of childhood acute lymphoblastic leukemia (ALL) have impaired adaptive physical function and poor health-related quality of life (HRQoL). Obesity may contribute to these impairments by increasing the physiological cost of walking. Due to treatment exposures during ALL therapy, survivors' cost of walking may be more impacted by obesity than the general population. Therefore, we examined associations between obesity, persistent motor neuropathy, and energy cost of walking; and examined associations between energy cost of walking, adaptive physical function, and HRQoL, in adult survivors of childhood ALL vs. community controls.MethodsObesity was measured via body mass index (BMI) and body fat percentage. The physiological cost index (PCI) was calculated from the six-minute walk test. Adaptive physical functioning was measured using two tests: the timed up and go (TUG) test and the physical performance test. Persistent motor neuropathy was measured using the modified total neuropathy score; HRQoL was measured using the Short-Form-36 questionnaire. The associations between obesity and PCI were evaluated using multivariable linear regressions in adult survivors of childhood ALL (n = 1,166) and community controls (n = 491). Then, the associations between PCI, adaptive physical functioning and peripheral neuropathy were examined using multivariable linear regressions. Finally, to determine the association between obesity, and neuropathy on PCI, while accounting for potential lifestyle and treatment confounders, a three model, sequential linear regression was used.ResultsObese individuals (BMI > 40 kg/m2 and excess body fat percentage [males: >25%; females: >33%]) had higher PCI compared to those with normal BMI and body fat percentage (0.56 ± 0.01 vs. 0.49 ± 0.009 beats/meter p < .01; and 0.51 ± 0.007 vs. 0.48 ± .0006 beats/meter p < .01, respectively). Treatment exposures did not attenuate this association. Increased PCI was associated with longer TUG time in survivors, but not community controls (6.14 ± 0.02 s vs. 5.19 ± 0.03 s, p < .01). Survivors with PCI impairment >95th percentile of community controls had lower HRQoL compared to un-impaired ALL survivors: 46.9 ± 0.56 vs. 50.4 ± 1.08, respectively (p < .01).ConclusionObesity was associated with increased PCI. Survivors with high PCI had disproportionately worse adaptive physical function and HRQoL compared to controls. Survivors with increased energy costs of walking may benefit from weight loss interventions.